Dental practice during Covid-19: Risks and measures - Eman KHEIR; Nada HASHIM (International Arab Journal of Dentistry (IAJD), 2020)
In December 2019, the novel coronavirus was discovered for the first time in Wuhan, China. On the 9th of January 2020, following a fast progression of the infection, the World Health Organization announced the finding to be a novel coronavirus that was named SARS-CoV-2.Dentistry has a very special working environment that puts it on the top of the lists of hazardous professions. The inherent nature of dental procedures might represent a transmission path for the virus. The spread of the disease can be prevented by taking strict measures before, during and after each dental procedure. The aim of this review is to shed a light on the possible modes of transmission of COVID-19 infection within the dental clinic. Additionally, the review highlights the necessary measures to keep the dental environment safe to dentists, patients and other personnel.